2015
DOI: 10.1093/neuonc/nov302
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine outcomes with proton and photon radiotherapy for standard risk medulloblastoma

Abstract: Proton radiotherapy may reduce the risk of some, but not all, radiation-associated late endocrine abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
104
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 33 publications
7
104
0
Order By: Relevance
“…1) (12). Changes in the delivery of radiation, such as the use of proton radiotherapy, may modify the risk or the latency period for the onset of HP axis dysfunction (13,14,15).…”
Section: Hp Axis Dysfunctionmentioning
confidence: 99%
“…1) (12). Changes in the delivery of radiation, such as the use of proton radiotherapy, may modify the risk or the latency period for the onset of HP axis dysfunction (13,14,15).…”
Section: Hp Axis Dysfunctionmentioning
confidence: 99%
“…Proton-based radiotherapy, a technique that seeks to exploit the decreased propensity of protons to travel beyond a targeted site in comparison to photons, has been recently introduced with the aim of decreasing even further the exposure of normal tissues located in proximity to the treated tumor [11]. Currently, only a limited number of institutions offer proton-based radiotherapy and only a small number of studies, all with short follow-up durations, have reported data on endocrine late effects in children treated with proton-based radiotherapy, so the long-term risks remain unknown [12, 13]. …”
Section: The Effect Of Radiotherapymentioning
confidence: 99%
“…Deficiencies in LH/FSH, TSH, and ACTH have been associated with HP radiotherapy at doses ≥30 Gy and hyperprolactinemia with even higher doses ≥40 Gy [17-19]. Efforts to improve the precision of the delivery of radiotherapy, as with the use of protons instead of photons, are likely to decrease scatter to the HP region and may hopefully reduce or delay the appearance of HP dysfunction especially in individuals treated for tumors located outside the HP region [13]. …”
Section: The Effect Of Radiotherapymentioning
confidence: 99%
See 2 more Smart Citations